Multifunctional MOF microneedle patch with adsorbed exosomes for enhanced diabetic wound healing - Jieyu Xiang; Ziming Li; songlu Tseng; Tianhao Li; Liquan Wang; Zhujun Li; Lin Kang; Fengzhou Du; Jiuzuo Huang; Nanze Yu; Xiao Long (Materials Today Bio)
Chronic wounds present a significant clinical challenge for which advanced dressings with regenerative properties are essential for effective healing. This study developed an exosome (Exo)-loaded microneedle (MN) patch. The patch was fabricated based on a metal-organic framework (MOF) through a self-assembly electrostatic adsorption process, with the objective of enhancing wound healing. The large surface area, high porosity, and positive charge of the MOF enable the efficient loading of negatively charged exosomes via electrostatic interactions. As the MNs degrade, the MOFs release both zinc ions, with antibacterial, anti-inflammatory, and angiogenic properties, and exosomes, which are internalized by cells and enhance cellular regeneration. In vitro and in vivo studies confirmed the effectiveness of the MN-MOF-Exo patch in diabetic wound healing, while RNA sequencing analysis revealed that the patch accelerated wound healing by upregulating key genes, activating the ERK1/2 and PI3K–Akt signaling pathways, and facilitating angiogenesis, cell migration, and extracellular matrix remodeling. This innovative approach combines the efficient electrostatic self-adsorption of exosomes onto the MOF within a MN structure, enabling the precise, minimally invasive, and effective delivery of therapeutic agents directly to the wound site. Furthermore, the regenerative mechanisms of the MN-MOF-Exo patch were investigated, revealing how tissue repair is promoted and how healing is accelerated through enhanced cellular regeneration and localized therapeutic effects.